2005
DOI: 10.1254/jphs.fpj05005x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Phosphoinositide 3-Kinase, Protein Kinase C, and Extracellular Signal-Regulated Kinase Is Required for Oridonin-Enhanced Phagocytosis of Apoptotic Bodies in Human Macrophage-Like U937 Cells

Abstract: Abstract. Our previous study showed that oridonin isolated from Rabdosia rubescens enhanced phagocytosis of apoptotic cells by macrophage-like U937 cells through tumor necrosis factor (TNF) α and interleukin (IL)-1β release. In this study, we further investigated signaling events involved in oridonin-augmented phagocytosis. Phagocytic stimulation was significantly suppressed by inhibitors, including a phosphoinositide 3-kinases (PI3K) inhibitor (wortmannin), a protein kinase C (PKC) inhibitor (stauroporine), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…These include PKCα in Fcγ receptormediated phagocytosis (Breton 2000) and in the IgG-stimulated respiratory burst (Larsen 2000), PKCβ in the phagocytosis of latex particles (Dieter 2000), and PKCβ and PKCδ in the phagocytosis of L. monocytogenes and translocation of PKCβ to early endosomes during bacterial escape from phagocytic vesicles (Wadsworth 2002). Novel PKCs δ and ε have also been linked to IgG-stimulated phagocytosis (Larsen 2000), and the phagocytosis of apoptotic cells by monocytes/macrophages requires PKC activity (Liu 2005). IL-4 induction of CD36 is blocked by PKC inhibition (Feng 2000), and IL-4 or IL-13 induces the activation of PKCδ and PKCζ (Ikizawa 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These include PKCα in Fcγ receptormediated phagocytosis (Breton 2000) and in the IgG-stimulated respiratory burst (Larsen 2000), PKCβ in the phagocytosis of latex particles (Dieter 2000), and PKCβ and PKCδ in the phagocytosis of L. monocytogenes and translocation of PKCβ to early endosomes during bacterial escape from phagocytic vesicles (Wadsworth 2002). Novel PKCs δ and ε have also been linked to IgG-stimulated phagocytosis (Larsen 2000), and the phagocytosis of apoptotic cells by monocytes/macrophages requires PKC activity (Liu 2005). IL-4 induction of CD36 is blocked by PKC inhibition (Feng 2000), and IL-4 or IL-13 induces the activation of PKCδ and PKCζ (Ikizawa 2001).…”
Section: Introductionmentioning
confidence: 99%
“…this suggests that rrE may have affected the immune response to the xenografts by recruiting immune cells to the tumor site. Supporting a possible involvement of oridonin in regulating immune cells and immune system, a previous study showed that oridonin enhanced the phagocytosis of apoptotic u937 cells by macrophage-like u937 cells through the release of tnF-α and il-1β (22).…”
Section: Discussionmentioning
confidence: 78%
“…Oridonin has been demonstrated to be able to cause ERK activation (12)(13)(14)(15) and p38 inactivation (13,15) in human macrophage-like U937 cells, murine fibrosarcoma L929 cells and human melanoma A375-S2 cells without affecting JNK activity (12,13,15). Other reports claimed that oridonin could inactivate JNK (15) in L929 cells, and inactivate ERK (11,16) but activate p38 and JNK (11) in human osteosarcoma cells and epidermoid carcinoma A431 cells.…”
Section: Discussionmentioning
confidence: 99%